Teaching Speaking Through Public Speaking Course - Iftakhar, Shampa (Stamford Journal of English, 2013)
In Bangladesh, English is taught as a foreign language. The English Language Teaching Improvement Project (ELTIP) introduced commutative textbooks in between 1992 to 2001 from class three to the higher secondary level. The main aim of ELTIP is to facilitate the teaching and learning of English with a methodology that will encourage students to acquire communicative competence in English through regular practice of these skills. Each of the books contains many tasks on speaking, but unfortunately in reality there is no practice and reflection of this skill. The speaking skill is never examined in S.S.C. and H.S.C. exam though in the English medium schools the scenario is totally opposite. Now the students who get admitted in the private universities having a very poor competency in speaking face great problems from the very beginning because English is the medium of instruction in these universities and general English courses are compulsory for all students. Very few students are capable of understanding lectures given in English. So conducting the class in English becomes a great challenge for all teachers. In my paper, I intend to analyse some factors that are closely related with teaching speaking. Then I will try to evaluate how Public Speaking course at Stamford University Bangladesh plays a vital role in teaching speaking, and our teachers and learners opinions regarding this course. DOI: http://dx.doi.org/10.3329/sje.v7i0.14473 Stamford Journal of English; Volume 7; Page 183-203